The formal sector wage premium and firm size for self-employed workers - Olivier Bargain; Eliane El Badaoui; Prudence Kwenda; Eric Strobl; Frank Walsh (Institute for the Study of Labor (IZA), 2012)
We develop a model where formal sector firms pay tax and informal ones do not, but informal firms risk incurring the penalty associated with non-compliance. Workers may enter self-employment or search for jobs as employees. Workers with higher managerial skills will run larger firms while workers with lower will manage smaller firms and will be in self-employment only when they cannot find a salary job. For these workers self-employment is a secondary/informal form of employment. The Burdett and Mortensen (1998) equilibrium search model turns out to be a special case that we amend by incorporating taxes and a penalty for non-payment of taxes. Our model is also consistent with some of the empirical literature in that the informal wage penalty does appear to be limited to low wage/skill workers while firm size is an important determinant of the employee formal sector premium. We test theoretical predictions using empirical evidence from Mexico and find that firm size wage effects for employees and self-employed workers are broadly consistent with the model.
Keywords: J31; O17; 330; informality; self-employment; Burdett and Mortensen model; Lohnstruktur; Informeller Sektor; Selbstständige; Betriebsgröße; Arbeitsplatzsuchmodell; Dualökonomie; Theorie